Circ_0096710 facilitates tumor growth via controlling ADAM10 expression in esophageal squamous cell carcinoma - Chaoqun Dong; Zhilong Li (Thoracic Cancer)
Abstract Background Esophageal squamous cell carcinoma (ESCC) is a global cancer related to the sixth largest cause of death. Circular RNAs (circRNAs) have affected the progress of ESCC during recent years, but the mechanism is not completely clear. So here we probed the effects of hsa_circ_0096710 (circ_0096710) in ESCC. Methods Relative levels of circ_0096710, miR‐1294, and ADAM10 were quantified by the quantitative real‐time reverse transcription‐polymerase chain reaction in ESCC tissues. Western blot assessed ADAM10, PCNA, MMP2, VEGFA, and OCT4 protein levels. Cell proliferative capacity was assessed by cell counting and cell colony‐forming assays. Transwell assays assessed cell migration and invasion. Angiogenesis was detected by tube formation assays. Stemness of cancer cells was estimated by sphere formation assays. Dual‐luciferin reporter and RNA immunoprecipitation assays determined the targeting relationship between miR‐1294 and circ_0096710 or ADAM10. Results Relative levels of circ_0096710 and ADAM10 mRNA were upregulated in ESCC cells, yet miR‐1294 was downregulated. Circ_0096710 silencing repressed ESCC cell proliferation, migration, invasion, angiogenesis, and stem‐like properties. Moreover, circ_0096710 was an upstream target of miR‐1294, and miR‐1294 inhibition reversed the role of circ_0096710 downregulation in ESCC cells. Furthermore, ADAM10 was a downstream target of miR‐1294, and miR‐1294 overexpression suppressed ESCC cell proliferation, migration, invasion, angiogenesis, and stem‐like properties by targeting ADAM10. Meanwhile, circ_0096710 upgraded ADAM10 expression through sponging miR‐1294. Also, circ_0096710 downregulation restrained tumor growth in mouse models. Conclusion Circ_0096710 upregulates ADAM10 via mediating miR‐1294 expression so as to accelerate the occurrence of ESCC, suggesting that circ_0096710 may be a potential therapeutic target for ESCC.